GAYA KEPEMIMPINAN DI MADRASAH ALIYAH: AUTHENTIC, TANSFORMATIONAL, AUTHORITARIAN ATAU TRANSACTIONAL? - Agus Purwanto; Masduki Asbari; Mirza Prameswari; Mohamad Ramdan (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2020)
The purpose of this study was to determine the effect of transformational, transactional, authentic and authoritarian leadership styles on teacher performance in a Madrasah Aliyah at Pati Central Java. The respondents of this study were 70 teachers and the method of data collection was by distributing electronic questionnaires to the teachers. Data analysis in this study uses SEM (Structural Equation Model) LISREL program version 8.70. The results of the analysis and processing of research data indicate that it shows that the leadership, transactional and authorian styles of Madrasah Aliyahdi Pati show a positive and significant effect on teacher performance while the transformational and authentic leadership styles do not significantly influence teacher performance. Keywords: Leadership Style Transformational, Transactional, Authentic Dan Authoritarian, Teacher Performance